Integrating artificial intelligence in education: How pre-service mathematics teachers use ChatGPT for 5E lesson plan design - Amine Nur Yanar; Özkan Ergene (Journal of Pedagogical Research)
This study examines the utilization of ChatGPT by pre-service mathematics teachers during the 5E lesson planning process, focusing on its affordances, constraints, and potential as a supportive tool in education. Twenty-one pre-service mathematics teachers, selected through purposive sampling, participated in the study. Data collection included 5E lesson plans, ChatGPT interaction transcripts, and participant interview responses, which were analyzed using content analysis within the framework of the instrumental approach. ChatGPT was utilized for lesson planning across categories addressing instructional and pedagogical content, encompassing fourteen distinct purposes distributed across the stages of the 5E lesson plan design: five for the engagement stage, five for exploration, six for explanation, five for elaboration, and four for evaluation. Interviews revealed both the affordances and constraints of ChatGPT, noting that while it provided creative and practical ideas, it often required well-structured prompts to yield relevant results. Despite its challenges, participants expressed their intention to use ChatGPT professionally to enhance lesson planning and instructional practices. ChatGPT is a valuable yet evolving tool for fostering innovation and efficiency in mathematics education, with implications for teacher training and future research on AI integration.